Competitive Dynamics and Factors Affecting Indonesian Black Tea Exports in The ASEAN Market - Putra Irwandi; Ninda Novita; Aulia Adetya (IPB University, 2025)
Indonesian black tea has a unique taste and quality, but its export dynamics in the ASEAN market are influenced by several factors, such as competition from other producing countries, quality comparisons, price fluctuations, and logistical challenges. This study examines the competitiveness of Indonesian black tea exports to ASEAN using panel data from 2010 to 2023. Data from Trademap with HS code 092030 for black tea and macroeconomic data from the World Bank were analyzed using Revealed Comparative Advantage (RCA) and Dynamic Revealed Comparative Advantage (DRCA). Additionally, a gravity model was used to assess the impact of economic and geographical variables on export volume. The results show fluctuating competitiveness, with a declining trend in recent years. DRCA analysis reveals a shift toward lower competitiveness compared to other tea-exporting countries. The gravity model shows that economic distance, inflation in other countries do not have a significant effect on Indonesia's export volume, while the GDP of other countries, population, and exchange rate of the destination country, and economic growth have a significant effect on export volume. The study suggests policy implications for expanding market share, improving product quality at the farm level, and strengthening international certifications to enhance competitiveness.